Improving Knowledge Of The Impact Of Early Marriage Among Adolescent: Podcast and Flipchart Methods - Siti Julaeha; Dian Priharja Putri (International Journal of Health and Pharmaceutical (IJHP), 2023)
Health promotion through reproductive health education can help increase adolescent girls’ knowledge about the impact of early marriage. Indonesia is one of the countries with the highest number of early marriages. Selection of effective health education media is an urgency as an effort to reduce the number of early marriages. This study aims to evaluate the effectiveness of health education using the podcast and flipchart methods. This study used a quasi-experimental with non-equivalent control group design which was carried out from December 2021 to January 2022 on 106 adolescent girls in Cibatur Keusik Village, Lebak Regency. Research respondents were divided into podcast groups and flipchart groups. In the podcast group, adolescent girls received health education using the audio method from the podcast while the flipchart group received the visual method from the flipchart. The analysis used in this study is univariate and bivariate. The results showed that the average value of the podcast group (32.49) was lower than the flipchart group (69.25). Statistically, it can be concluded that health education using the flipchart method is more effective than the podcast method (p=0.000; t=-6.21; df=104). Health education using the flipchart method is more effective than the podcast method. The method can be used by health promoters to improve adolescents' understanding of the impact of early marriage.